Chemical Composition of Bamboo Seeds (Bambusa arundinacea Willd.) - Mitra, G. N.; Nayak, Y (Indian Forester, 1972)
Bamboo seeds produced in Chandka range of Puri Forest Division (Orissa) were analysed for their chemical composition. The bamboo seeds were found to be comparable to wheat in their protein content but to rice In their protein quality. The bamboo plants (Bambusa arundinacea Willd.) In Cbandka range of Puri Forest Division, Orissa came to gregarlous flowering in the summer of 1969 after forty years. The bamboo seeds produced were widely consumed by the local population. It was therefore thought worthwhile to examine the chemical composition of these seeds. Chemical composition of bamboo seeds produced in U.P. and Mysore have been reported (Rao et al., 1955; Rae et a1., 1969). No information is however available about the chemical composition of bamboo seeds produced in Eastern India.